Estimating unrecorded human-caused mortalities of grizzly bears in the Flathead Valley, British Columbia, Canada - McLellan,Bruce N.; Mowat,Garth; Lamb,Clayton T. (PeerJ, 2018)
Managing the number of grizzly bear (Ursus arctos) mortalities to a sustainable level is fundamental to bear conservation. All known grizzly bear deaths are recorded by management agencies but the number of human-caused grizzly bear deaths that are not recorded is generally unknown, causing considerable uncertainty in the total number of mortalities. Here, we compare the number of bears killed legally by hunters to the number killed by people for all other reasons, for bears wearing functioning radiocollars and for uncollared bears recorded in the British Columbia (BC) government mortality database for the Flathead Valley in southeast BC. Between 1980 and 2016, permitted hunters killed 10 collared bears and 12 (9 known, 3 suspected) were killed by people for other reasons. This ratio differed (p < 0.0001) from the uncollared bears in the government database where 71 were killed by hunters while only 10 were killed for other reasons. We estimate that 88% (95% CI; 67–96%) of the human-caused mortalities that were not by permitted hunters were unreported. The study area may have low reporting rates because it is >40 km on a gravel road from a Conservation Officer office, so reporting is difficult and there are no human residences so there is little concern of a neighbor contacting an officer. Our results are likely indicative of other places that are road-accessed but far from settlements. We discuss the implications of sampling individuals for collaring and the possible implications of wearing a collar on the animal’s fate.
Keywords: British Columbia; Grizzly bear; Human-caused mortality; Ursus arctos; Reporting rates; Cryptic killing; Unknown fates